REPORTING ON SEXUAL VIOLENCE AGAINST WOMEN IN ONLINE MEDIA, STUDY OF CRITICAL DISCOURSE ANALYSIS BY SARA MILLS: PEMBERITAAN KEKERASAN SEKSUAL PADA PEREMPUAN DI MEDIA ONLINE, STUDI ANALISIS WACANA KRITIS MODEL SARA MILLS - Avita Aniqotul 'Athiyyah; Abdul Muntaqim Al Anshory (LLDIKTI Wilayah X, 2024)
This research aims to reveal media bias representations in the discourse of reporting on sexual violence against women in the online media platform detik Jatim using Sara Mills' critical discourse analysis model. The study employs a qualitative descriptive research approach. Data collection techniques include reading and note-taking, with data analysis stages comprising data reduction, data presentation, and drawing conclusions. Primary data sources consist of news articles covering murders with a motive of sexual violence committed by a male in-law against a female relative, as reported in detikJatim's online media from November 1, 2023, to November 8, 2023. Secondary data sources are derived from relevant previous studies. The results of this research include 8 news articles depicting the positions of subjects-objects and the positions of authors-readers within the discourse. The diverse forms of reporting discourse range from motives behind the murders, investigator responses, perpetrator responses, responses from the victim's parents, psychological perspectives, perspectives from practitioners of women and child protection, perspectives from the National Commission on Violence Against Women (Komnas Perempuan), to personal messages from the victims.